Topicality of the use of adaptive technologies in training Masters in intellectual property management - Bruyeva, V. (Problems of Engineer-Pedagogical Education, 2019)
The article is devoted to the topical question of training master‟s students specializing in intellectual property management, the feasibility of introducing adaptive technologies into the organization of the educational process while training such professionals. The paper analyzes various requirements for modern intellectual property management professionals in terms of the intellectual property market demand and the supply provided by higher education institutions. Based on the analysis of legislative and normative regulations, educational and methodological materials, scientific sources, educational and professional master's degree programs in intellectual property management, we have identified a complex of competencies which is integrated according to the standards and taking into account market requirements, the demand of employers, the supply provided by institutions of higher education and should be mastered by students while doing their Master‟s degree course. It has been determined that professional training of masters in intellectual property management needs improvement. The article establishes that, during the educational process, masters in intellectual property management are expected to acquire knowledge and skills which will enable them to use and combine a wide range of industries (management, law, economics, engineering, etc.). Therefore, the paper reveals the topicality of implementing adaptive technologies during the process of professional training of masters in intellectual property management. It is argued that incorporation of adaptive technologies in the organization of the educational process will allow coordinating the common goals and objectives of "employers and educational institutions" with the aim of developing relevant competencies of future professionals, and, eventually, will provide the intellectual property market with professional managers who will be able to continue self-education and self-organization throughout their professional life. Some requirements for intellectual property management professionals are considered in accordance with international standards and a rapid change in the vector of development of domestic businesses for the purpose of international integration. The emphasis is placed on the expediency of continuous monitoring and modernization of content, forms and methods of teaching in the process of training masters in intellectual property management in accordance with national and international standards.